Ceramic material, preparation method thereof and application of ceramic material in piezoelectricity

By adopting composite doping technology in ceramic materials, combining BI (SB1/3LN2/3) O3 and SR2fe1-Zalzmoo6, the problem of poor pollution and performance in existing voltage ceramic materials has been solved. Increased density and voltage performance.

CN119330703AInactive Publication Date: 2025-01-21HUNAN MEICHENG NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411866013.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-01-21
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing lead zirconium titanate piezoelectric ceramic materials are prone to produce PbO volatile pollutants during sintering or use, and the sintering temperature of barium titanate is high and the piezoelectric performance is poor, which limits its wide application.

Method used

The general chemical structure formula of a ceramic material is used (1-α-β)(Ba1-xMx)[Ti1-y(W1/2Cu1/2)y]O3-αBi(Sb1/3Ln2/3)O3-βSr2Fe1-zAlzMoO6 ,Pass BaTiO3 is compositely doped with peralkaline earth metal elements and (W1/2Cu1/2)4+, combined with the doping of Bi(Sb1/3Ln2/3)O3 and Sr2Fe1-zAlzMoO6, to form a dense ceramic material and improve the piezoelectric performance.

Benefits of technology

The density of ceramic materials and the improvement of piezoelectric properties have been achieved, the sintering temperature is reduced, and the application needs of the piezoelectric ceramic sensor and converter are met.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330703A_ABST
    Figure CN119330703A_ABST
Patent Text Reader

Abstract

The invention relates to the field of ceramic materials, in particular to a ceramic material and a preparation method and application thereof in piezoelectrics, the chemical structural general formula of the ceramic material is as follows: (1-alpha-beta) (Ba1-xMx) [Ti1-y (W1 / 2Cu1 / 2) y] O3-alpha Bi (Sb1 / 3Ln2 / 3) O3-beta Sr2Fe1-zAlzMoO6, M is an alkaline earth metal element; ln is a lanthanide rare earth element; x is equal to 0.12, y is equal to 0.04, z is equal to 0.2, alpha is larger than or equal to 0.01 and smaller than or equal to 0.1, beta is larger than 0 and smaller than or equal to 0.05, and the ceramic material is good in compactness and excellent in piezoelectric performance and can meet the application requirements of piezoelectric ceramic sensors, piezoelectric ceramic transducers and other devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ceramic materials, in particular to a ceramic material and a preparation method thereof and application in piezoelectricity. Background Art

[0002] Piezoelectric ceramics are functional materials that can convert electrical energy into mechanical energy and vice versa. They are currently widely used in sensors, transducers, drivers, filters, medical devices and other equipment. Among them, lead zirconate titanate piezoelectric ceramics are currently the more mainstream piezoelectric ceramic materials, but they are very likely to produce volatile pollutants such as PbO during sintering or use, which not only seriously pollutes the environment but also harms human health, so they need to be replaced by safer lead-free piezoelectric materials.

[0003] Barium titanate (BaTiO3) is a relatively early discovered lead-free piezoelectric material and has been widely used before the discovery of PZT. However, the sintering temperature of BaTiO3 is often above 1300°C, which makes it difficult to co-fire with cheap conductive metal electrode materials (such as copper, nickel, iron, etc.), and its piezoelectric performance is far inferior to that of lead zirconate titanate, which seriously restricts its widespread application. Summary of the invention

[0004] Purpose of the invention: In view of the above technical problems, the present invention proposes a ceramic material and a preparation method thereof and an application in piezoelectrics.

[0005] The technical solutions adopted are as follows: A ceramic material, the general chemical structure of which is shown below: (1-α-β)(Ba 1-x M x )[Ti 1-y (W 1 / 2 Cu 1 / 2 ) y ]O3-αBi(Sb 1 / 3 Ln 2 / 3 )O3-βSr2Fe 1-z Al z MoO6 Wherein, M is an alkaline earth metal element; Ln is a lanthanide rare earth element; x=0.12, y=0.04, z=0.2, 0.01≤α≤0.1, 0<β≤0.05.

[0006] Furthermore, M is Ca and / or Sr.

[0007] Furthermore, Ln is any one of Sm, Eu, Gd, Tb, Dy, and Ho, or a combination of two or more thereof.

[0008] Furthermore, 0.04≤α≤0.06, 0.01≤β≤0.03.

[0009] Furthermore, α=0.05, β=0.02.

[0010] The present invention also provides a method for preparing a ceramic material: BaCO3, MCO3, TiO2, WO6 and CuO are mixed and ball-milled, dried and pre-calcined at 850-950°C for 1-5h to obtain a first mixture; The mixture of Bi2O3, Sb2O3 and Ln2O3 is ball-milled, dried and pre-calcined at 950-1050°C for 1-5h to obtain a second mixture; Sr(NO3)2、(NH4)6MoO7O 24 ·4H2O, Al(NO3)3·9H2O, and Fe(NO3)3·9H2O are dissolved in deionized water, and then nitric acid, citric acid, and ethylene glycol are added to obtain a mixed solution, the mixed solution is stirred and reacted at 60-80°C for 1-5h to obtain a sol, the sol is dried and then sintered at 600-650°C for 1-5h, and then pre-sintered at 800-850°C for 1-5h to obtain a third mixture; The first mixture, the second mixture and the third mixture are mixed and ball-milled, and then dried. A binder is added to granulate, sieve and press to obtain a green body. The green body is first heated to 600-650° C. for heat preservation and debinding for 1-5 hours, and then heated to 1100-1200° C. for heat preservation and sintering for 1-5 hours.

[0011] Furthermore, the heating rate in the first stage of heating is 1-5°C / min, and the heating rate in the second stage of heating is 10-30°C / min.

[0012] The present invention also provides the use of the above ceramic material in preparing a piezoelectric ceramic sensor or a piezoelectric ceramic transducer.

[0013] Beneficial effects of the present invention: The present invention provides a ceramic material, using alkaline earth metal elements and (W 1 / 2 Cu 1 / 2 ) 4+ Composite doping of BaTiO3 can completely solid-solution increase the density of ceramic materials and reduce their inherent defects, thus improving piezoelectric properties; Bi(Sb 1 / 3 Ln 2 / 3)O3 as a new component can induce the formation of a rhombohedral phase. The ceramic material can show the strongest piezoelectric properties near the rhombohedral-tetragonal phase boundary. Both of them have a perovskite structure. They can not only form a single and stable perovskite structure by solid solution, but also control the degree of lattice distortion by doping rare earth ions, so that the movement of electric domains is effectively improved, thereby further improving the piezoelectric properties of piezoelectric ceramics and helping to obtain a denser and more uniform microstructure. Sr2Fe 1-z Al z MoO6 is a double perovskite compound that can give full play to the doping effect of multi-component ions during the solid solution process, inducing the transformation of the BaTiO3 matrix phase structure, thereby greatly improving the piezoelectric properties of the ceramic material; When the sintering temperature is low, the ceramic material is not completely sintered, and there are many microstructural defects such as microcracks and holes, so the density is low. When the temperature is too high, the grains grow too large. Due to the interaction between the grain boundaries, the densification of the crystals will in turn be inhibited. In this application, controlling the sintering temperature to 1100-1200°C can obtain a ceramic material with good density and excellent piezoelectric properties, which can meet the application requirements of equipment such as piezoelectric ceramic sensors and piezoelectric ceramic transducers. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is the SEM image of the ceramic material prepared in Example 1. DETAILED DESCRIPTION

[0015] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially. The techniques not mentioned in the present invention are all referenced to the prior art. Unless otherwise specified, the following examples and comparative examples are parallel experiments, using the same processing steps and parameters.

[0016] Embodiment 1: This embodiment provides a ceramic material, the general chemical structure of which is shown below: 0.93(Ba 0.88 Sr 0.12 )[Ti 0.96 (W 1 / 2 Cu 1 / 2 ) 0.04 ]O3-0.05Bi(Sb 1 / 3 Dy 2 / 3 )O3-0.02Sr2Fe 0.8 Al 0.2 MoO6 The preparation method of the above ceramic material is as follows: BaCO3, SrCO3, TiO2, WO6, and CuO are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 900°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a first mixture; Bi2O3, Sb2O3 and Dy2O3 are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 1000°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a second mixture; Weigh Sr(NO3)2, (NH4)6MoO7O 24 ·4H2O, Al(NO3)3·9H2O, Fe(NO3)3·9H2O as raw materials, dissolve the raw materials in 20 times the mass of deionized water, and then add 10 times the mass of (NH4)6MoO7O 24 · 4H2O mass of nitric acid, 1.1 times the mass of cations of citric acid and 5% of the mass of ethylene glycol to obtain a mixed solution, stirring the mixed solution at 80°C for 2 hours to obtain a sol, drying the sol, sintering at 600°C for 2 hours, and then pre-sintering at 850°C for 2 hours to obtain a third mixture; The first mixture, the second mixture and the third mixture are added into the ball milling jar of a planetary ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled for 10 hours and then dried in an oven, and then 8wt% polyvinyl alcohol solution is added as a binder for granulation. After passing through an 80-mesh sieve, the green body is pressed into a green body under a pressure of 100 MPa, and the green body is first heated to 650°C at a rate of 2°C / min in one stage and kept for 2 hours to debind, and then heated to 1150°C at a rate of 20°C / min in a second stage and kept for sintering for 2 hours.

[0017] Embodiment 2: This embodiment provides a ceramic material, the general chemical structure of which is shown below: 0.93(Ba 0.88 Sr 0.12 )[Ti 0.96 (W 1 / 2 Cu 1 / 2 ) 0.04 ]O3-0.05Bi(Sb 1 / 3 Ho 2 / 3 )O3-0.02Sr2Fe 0.8 Al 0.2 MoO6 The preparation method of the above ceramic material is as follows: BaCO3, SrCO3, TiO2, WO6, and CuO are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 900°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a first mixture; Bi2O3, Sb2O3 and Ho2O3 are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 1000°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a second mixture; Weigh Sr(NO3)2, (NH4)6MoO7O 24 ·4H2O, Al(NO3)3·9H2O, Fe(NO3)3·9H2O as raw materials, dissolve the raw materials in 20 times the mass of deionized water, and then add 10 times the mass of (NH4)6MoO7O 24 · 4H2O mass of nitric acid, 1.1 times the mass of cations of citric acid and 5% of the mass of ethylene glycol to obtain a mixed solution, stirring the mixed solution at 80°C for 2 hours to obtain a sol, drying the sol, sintering at 600°C for 2 hours, and then pre-sintering at 850°C for 2 hours to obtain a third mixture; The first mixture, the second mixture and the third mixture are added into the ball milling jar of a planetary ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled for 10 hours and then dried in an oven, and then 8wt% polyvinyl alcohol solution is added as a binder for granulation. After passing through an 80-mesh sieve, the green body is pressed into a green body under a pressure of 100 MPa, and the green body is first heated to 650°C at a rate of 2°C / min in one stage and kept for 2 hours to debind, and then heated to 1150°C at a rate of 20°C / min in a second stage and kept for sintering for 2 hours.

[0018] Embodiment 3: This embodiment provides a ceramic material, the general chemical structure of which is shown below: 0.93(Ba 0.88 Sr 0.12 )[Ti 0.96 (W 1 / 2 Cu 1 / 2 ) 0.04 ]O3-0.05Bi(Sb 1 / 3 Dy 2 / 3 )O3-0.02Sr2Fe 0.8 Al 0.2 MoO6 The preparation method of the above ceramic material is as follows: BaCO3, SrCO3, TiO2, WO6, and CuO are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 900°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a first mixture; Bi2O3, Sb2O3 and Dy2O3 are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 1000°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a second mixture; Weigh Sr(NO3)2, (NH4)6MoO7O 24 ·4H2O, Al(NO3)3·9H2O, Fe(NO3)3·9H2O as raw materials, dissolve the raw materials in 20 times the mass of deionized water, and then add 10 times the mass of (NH4)6MoO7O 24 · 4H2O mass of nitric acid, 1.1 times the mass of cations of citric acid and 5% of the mass of ethylene glycol to obtain a mixed solution, stirring the mixed solution at 80°C for 2 hours to obtain a sol, drying the sol, sintering at 600°C for 2 hours, and then pre-sintering at 850°C for 2 hours to obtain a third mixture; The first mixture, the second mixture and the third mixture are added into the ball milling jar of a planetary ball mill, anhydrous ethanol is used as the ball milling medium, mixed and ball milled for 10 hours and then dried in an oven, 8wt% polyvinyl alcohol solution is added as a binder for granulation, and after passing through an 80-mesh sieve, pressed into a green body at a pressure of 100 MPa, and the green body is first heated to 650°C at a speed of 2°C / min in one stage and kept for 2 hours to debind, and then heated to 1100°C at a speed of 20°C / min in a second stage and kept for sintering for 2 hours.

[0019] Embodiment 4: This embodiment provides a ceramic material, the general chemical structure of which is shown below: 0.93(Ba 0.88 Sr 0.12 )[Ti 0.96 (W 1 / 2 Cu 1 / 2 ) 0.04 ]O3-0.05Bi(Sb 1 / 3 Dy 2 / 3 )O3-0.02Sr2Fe 0.8 Al 0.2 MoO6 The preparation method of the above ceramic material is as follows: BaCO3, SrCO3, TiO2, WO6, and CuO are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 900°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a first mixture; Bi2O3, Sb2O3 and Dy2O3 are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 1000°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a second mixture; Weigh Sr(NO3)2, (NH4)6MoO7O 24 ·4H2O, Al(NO3)3·9H2O, Fe(NO3)3·9H2O as raw materials, dissolve the raw materials in 20 times the mass of deionized water, and then add 10 times the mass of (NH4)6MoO7O 24 · 4H2O mass of nitric acid, 1.1 times the mass of cations of citric acid and 5% of the mass of ethylene glycol to obtain a mixed solution, stirring the mixed solution at 80°C for 2 hours to obtain a sol, drying the sol, sintering at 600°C for 2 hours, and then pre-sintering at 850°C for 2 hours to obtain a third mixture; The first mixture, the second mixture and the third mixture are added into the ball milling jar of a planetary ball mill, anhydrous ethanol is used as the ball milling medium, mixed and ball milled for 10 hours and then dried in an oven, 8wt% polyvinyl alcohol solution is added as a binder for granulation, and after passing through an 80-mesh sieve, pressed into a green body under a pressure of 100 MPa, and the green body is first heated to 650°C at a rate of 2°C / min in one stage and kept for 2 hours for debinding, and then heated to 1200°C at a rate of 20°C / min in a second stage and kept for sintering for 2 hours.

[0020] Comparative Example 1: The same as Example 1, except that Bi(Sb 1 / 3 Dy 2 / 3 )O3 and Sr2Fe 0.8 Al 0.2 MoO6.

[0021] This comparative example provides a ceramic material, the general chemical structure of which is shown below: (Ba 0.88 Sr 0.12 )[Ti 0.96 (W 1 / 2 Cu 1 / 2 ) 0.04 ]O3 The preparation method of the above ceramic material is as follows: BaCO3, SrCO3, TiO2, WO6, and CuO are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 900°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a first mixture; The first mixture is added into the ball milling jar of a planetary ball mill, with anhydrous ethanol as the ball milling medium, and after mixing and ball milling for 10 hours, it is dried in an oven, and then 8wt% polyvinyl alcohol solution is added as a binder to granulate. After passing through an 80-mesh sieve, it is pressed into a green body under a pressure of 100 MPa. The green body is first heated to 650°C at a rate of 2°C / min in one stage and kept for 2 hours to debind, and then heated to 1150°C at a rate of 20°C / min in a second stage and kept for sintering for 2 hours.

[0022] Comparative Example 2: The same as Example 1, except that Bi(Sb 1 / 3 Dy 2 / 3 )O3.

[0023] Comparative Example 3: The same as Example 1, except that Sr2Fe 0.8 Al 0.2 MoO6.

[0024] Comparative Example 4: The same as Example 1, except that (Ba 0.88 Sr 0.12 )TiO3 replaces (Ba 0.88 Sr 0.12 )[Ti 0.96 (W 1 / 2 Cu 1 / 2 ) 0.04 ]O3.

[0025] This comparative example provides a ceramic material, the general chemical structure of which is shown below: 0.93(Ba 0.88 Sr 0.12 )TiO3-0.05Bi(Sb 1 / 3 Dy 2 / 3 )O3-0.02Sr2Fe 0.8 Al 0.2 MoO6 The preparation method of the above ceramic material is as follows: BaCO3, SrCO3 and TiO2 are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 900°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a first mixture; Bi2O3, Sb2O3 and Dy2O3 are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 1000°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a second mixture; Weigh Sr(NO3)2, (NH4)6MoO7O 24 ·4H2O, Al(NO3)3·9H2O, Fe(NO3)3·9H2O as raw materials, dissolve the raw materials in 20 times the mass of deionized water, and then add 10 times the mass of (NH4)6MoO7O 24 · 4H2O mass of nitric acid, 1.1 times the mass of cations of citric acid and 5% of the mass of ethylene glycol to obtain a mixed solution, stirring the mixed solution at 80°C for 2 hours to obtain a sol, drying the sol, sintering at 600°C for 2 hours, and then pre-sintering at 850°C for 2 hours to obtain a third mixture; The first mixture, the second mixture and the third mixture are added into the ball milling jar of a planetary ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled for 10 hours and then dried in an oven, and then 8wt% polyvinyl alcohol solution is added as a binder for granulation. After passing through an 80-mesh sieve, the green body is pressed into a green body under a pressure of 100 MPa, and the green body is first heated to 650°C at a rate of 2°C / min in one stage and kept for 2 hours to debind, and then heated to 1150°C at a rate of 20°C / min in a second stage and kept for sintering for 2 hours.

[0026] Comparative Example 5: The same as Example 1, except that BiSbO3 is used instead of Bi(Sb 1 / 3 Dy 2 / 3 )O3.

[0027] This comparative example provides a ceramic material, the general chemical structure of which is shown below: 0.93(Ba 0.88 Sr 0.12 )[Ti 0.96 (W 1 / 2 Cu 1 / 2 ) 0.04 ]O3-0.05BiSbO3-0.02Sr2Fe 0.8 Al 0.2 MoO6 The preparation method of the above ceramic material is as follows: BaCO3, SrCO3, TiO2, WO6, and CuO are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 900°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a first mixture; Bi2O3 and Sb2O3 were added into a ball mill of a planetary ball mill, anhydrous ethanol was used as a ball milling medium, the mixture was ball milled for 10 hours, and then dried in an oven, and then the mixture was heated to 1000°C at a rate of 10°C / min in a muffle furnace and pre-calcined for 2 hours to obtain a second mixture; Weigh Sr(NO3)2, (NH4)6MoO7O 24 ·4H2O, Al(NO3)3·9H2O, Fe(NO3)3·9H2O as raw materials, dissolve the raw materials in 20 times the mass of deionized water, and then add 10 times the mass of (NH4)6MoO7O 24 · 4H2O mass of nitric acid, 1.1 times the mass of cations of citric acid and 5% of the mass of ethylene glycol to obtain a mixed solution, stirring the mixed solution at 80°C for 2 hours to obtain a sol, drying the sol, sintering at 600°C for 2 hours, and then pre-sintering at 850°C for 2 hours to obtain a third mixture; The first mixture, the second mixture and the third mixture are added into the ball milling jar of a planetary ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled for 10 hours and then dried in an oven, and then 8wt% polyvinyl alcohol solution is added as a binder for granulation. After passing through an 80-mesh sieve, the green body is pressed into a green body under a pressure of 100 MPa, and the green body is first heated to 650°C at a rate of 2°C / min in one stage and kept for 2 hours to debind, and then heated to 1150°C at a rate of 20°C / min in a second stage and kept for sintering for 2 hours.

[0028] Comparative Example 6: The same as Example 1, except that Sr2FeMoO6 is used instead of Sr2Fe 0.8 Al 0.2 MoO6.

[0029] This comparative example provides a ceramic material, the general chemical structure of which is shown below: 0.93(Ba 0.88 Sr 0.12 )[Ti 0.96 (W 1 / 2 Cu 1 / 2 ) 0.04 ]O3-0.05Bi(Sb 1 / 3 Dy 2 / 3 )O3-0.02Sr2FeMoO6 The preparation method of the above ceramic material is as follows: BaCO3, SrCO3, TiO2, WO6, and CuO are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 900°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a first mixture; Bi2O3, Sb2O3 and Dy2O3 are added into a ball mill of a planetary ball mill, anhydrous ethanol is used as a ball milling medium, mixed and ball milled for 10 hours, dried in an oven, and then heated to 1000°C in a muffle furnace at a speed of 10°C / min and pre-calcined for 2 hours to obtain a second mixture; Weigh Sr(NO3)2, (NH4)6MoO7O 24 ·4H2O, Fe(NO3)3·9H2O as raw materials, dissolve the raw materials in 20 times the mass of deionized water, and then add 10 times the mass of (NH4)6MoO7O 24 · 4H2O mass of nitric acid, 1.1 times the mass of cations of citric acid and 5% of the mass of ethylene glycol to obtain a mixed solution, stirring the mixed solution at 80°C for 2 hours to obtain a sol, drying the sol, sintering at 600°C for 2 hours, and then pre-sintering at 850°C for 2 hours to obtain a third mixture; The first mixture, the second mixture and the third mixture are added into the ball milling jar of a planetary ball mill, with anhydrous ethanol as the ball milling medium, mixed and ball milled for 10 hours and then dried in an oven, and then 8wt% polyvinyl alcohol solution is added as a binder for granulation. After passing through an 80-mesh sieve, the green body is pressed into a green body under a pressure of 100 MPa, and the green body is first heated to 650°C at a rate of 2°C / min in one stage and kept for 2 hours to debind, and then heated to 1150°C at a rate of 20°C / min in a second stage and kept for sintering for 2 hours.

[0030] Performance test: The surfaces of the ceramic materials prepared in Examples 1-4 and Comparative Examples 1-6 were polished, coated with silver paste on both sides, kept at 750°C for 10 min, and finally polarized at a DC voltage of 4 kV / mm for 20 min in silicone oil at 120°C and placed for 24 hours as samples to test their performance.

[0031] The room temperature piezoelectric constant of the sample was measured using a ZJ-3AN quasi-static piezoelectric constant tester. d 33 ; The electromechanical coupling coefficient kp, mechanical quality factor Qm and dielectric loss tanδ (25°C, 1V, 1kHz) of the samples were measured and analyzed using a precision impedance analyzer (Agilent HP4294A). The test results are shown in Table 1 below: ; As can be seen from Table 1 above, the ceramic material prepared by the present invention has excellent piezoelectric properties; From the comparison of Examples 1-2, it can be seen that doping with different lanthanide rare earth elements will affect the piezoelectric properties of ceramic materials; From the comparison between Examples 1 and 3-4, it can be seen that different sintering temperatures will affect the piezoelectric properties of the ceramic material. When the sintering temperature is 1150°C, the piezoelectric properties of the ceramic material are optimal. From the comparison between Example 1 and Comparative Examples 1-3, it can be seen that Bi(Sb 1 / 3 Dy 2 / 3 )O3 and Sr2Fe 0.8 Al 0.2 The addition of MoO6 plays a positive role in improving the piezoelectric properties of ceramic materials; From the comparison between Example 1 and Comparative Examples 4-6, it can be seen that Sr 2+ ,(W 1 / 2 Cu 1 / 2 ) 4+ 、Dy 3+ and Al 3+ The introduction of has played a positive role in improving the piezoelectric properties of ceramic materials.

[0032] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A ceramic material, characterized in that: Its chemical structure is shown below: (1-α-β)(Ba 1-x M x )[Ti 1-y (W 1 / 2 The 1 / 2 ) y ]O3-αBi(Sb 1 / 3 Ln 2 / 3 )O3-βSr2Fe 1-z Al z MoO6 Wherein, M is an alkaline earth metal element; Ln is a lanthanide rare earth element; x=0.12, y=0.04, z=0.2, 0.01≤α≤0.1, 0<β≤0.

05.

2. The ceramic material according to claim 1, characterized in that M is Ca and / or Sr.

3. The ceramic material according to claim 1, characterized in that Ln is any one of Sm, Eu, Gd, Tb, Dy, and Ho, or a combination of two or more thereof.

4. The ceramic material according to claim 1, characterized in that 0.04≤α≤0.06,0.01≤β≤0.03。 5. The ceramic material according to claim 1, characterized in that α=0.05,β=0.02。 6. A method for preparing a ceramic material as claimed in any one of claims 1 to 5, characterized in that: The details are as follows: BaCO3, MCO3, TiO2, WO6 and CuO are mixed and ball-milled, dried and pre-calcined at 850-950°C for 1-5h to obtain a first mixture; The mixture of Bi2O3, Sb2O3 and Ln2O3 is ball-milled, dried and pre-calcined at 950-1050°C for 1-5h to obtain a second mixture; Sr(NO3)2、(NH4)6MoO7O 24 ·4H2O, Al(NO3)3·9H2O, and Fe(NO3)3·9H2O are dissolved in deionized water, and then nitric acid, citric acid, and ethylene glycol are added to obtain a mixed solution, the mixed solution is stirred and reacted at 60-80°C for 1-5h to obtain a sol, the sol is dried and then sintered at 600-650°C for 1-5h, and then pre-sintered at 800-850°C for 1-5h to obtain a third mixture; The first mixture, the second mixture and the third mixture are mixed and ball-milled, and then dried. A binder is added to granulate, sieve and press to obtain a green body. The green body is first heated to 600-650° C. for heat preservation and debinding for 1-5 hours, and then heated to 1100-1200° C. for heat preservation and sintering for 1-5 hours.

7. The method for preparing a ceramic material according to claim 6, characterized in that: The heating rate during the first stage of heating is 1-5°C / min, and the heating rate during the second stage of heating is 10-30°C / min.

8. Use of the ceramic material according to any one of claims 1 to 5 in preparing a piezoelectric ceramic sensor or a piezoelectric ceramic transducer.

Citation Information

Cited By

  • Piezoelectric ceramic for new energy automobile and preparation method thereof

    CN121405456A

  • Piezoelectric ceramic for new energy vehicle and preparation method thereof

    CN121405456B